FRI0238 The effect of rituximab on lipid levels in patients with rheumatoid arthritis. (23rd January 2014) - Kostoglou-Athanassiou, I.; Tzanavari, A.; Basdragianni, D.; Papadaki, A.; Dadiras, N.; Athanassiou, P.
Abstract : Background: Rheumatoid arthritis (RA) is known to be associated with cardiovascular comorbidity. In particular, patients with RA are known to be at increased for the development of atherosclerosis. Treatment with biological agents in RA may affect lipid levels. Objectives: The aim was to study the effect of rituximab treatment on lipid levels in RA patients. Methods: In a cohort of 20 patients with RA lipid levels were studied before, 6 and 12 months after treatment with the biological agent rituximab (2x1000 mg i.v. infusions 2 wks apart) at baseline, 6 and 12 months later. All patients fulfilled the 2010 ACR/EULAR criteria for RA. Total cholesterol, HDL, LDL cholesterol and triglyceride levels were measured at baseline, 6 and 12 months later. Results: At baseline total cholesterol was 207.41±8.33 mg/dl (mean±SEM), 6 months and 12 months later increasing to 218.27±7.02 and 226.12±8.71 mg/dl, respectively (p<0.001, Student's t test). At baseline HDL cholesterol was 59.17±3.31 mg/dl, 6 and 12 months later increasing to 66.05±3.49 and 58.81±3.04 mg/dl, respectively (p<0.001). At baseline LDL cholesterol was 122.89±8.96 mg/dl, 6 and 12 months later increasing to 124.58±5.61 and 141.56±7.95 mg/dl, respectively (p<0.001). At baseline triglyceride levels were 138.50±13.91 mg/dl, 6 and 12 months later decreasing to 122.55±10.52 and 118.65±9.91 mg/dl, respectively (p<0.001). Conclusions: Treatment with the biological agent rituximab in RA resulted in an increase in total cholesterol, paralleled by an increase in HDL cholesterol, LDL cholesterol, while triglyceride levels decreased. The adverse effect on total cholesterol levels may be counteracted by the parallel increase in HDL thus conferring a beneficial effect on the patients as far as cardiovascular risk is concerned. These findings have therapeutic implications as the effect of rituximab on lipid levels may render systematic treatment with statins necessary in rheumatoid arthritis. Disclosure of Interest : None Declared